Materials in progress : innovations for designers and architects - Peters, Sascha; Drewes, Diana (Birkhäuser, 2019)
New materials and technologies play a significant role in architecture and design. Environmentally compatible materials and production methods are demanded just as much as smoothly functioning recycling management. In addition, trends like digitalization, 3D printing and intelligent systems and materials have a decisive influence on material innovations. The book's eight chapters span a bridge from science and industrial research to applications in architecture and design. In a compact format, it offers a well-grounded overview of the latest material innovations, including edible packaging, liquid light and intelligent natural materials. At the same time, the societal dimension of such developments is taken into consideration.